Selection Strategies and Organizational Management in the Private Sector: Applying the Matching Theory in the Recruitment Process - Edih University; Onoriode o. Humphrey; Faghawari Nyanayon (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The study examined selection strategies and organizational management in the private sector: applying the matching theory in the recruitment process. The population of study is the staff of the 50 selected organizations who were administered structured questionnaire. The Taro Yamane's formular for finite population was employed to achieve the 350 sample size used for the study. Correlation and Multiple regressions analyses were used to analyze primary data generated from the field and test thetwo formulated hypotheses. The study found that selection strategies had positive and significant effects on organizational management or performance in the selected hotels in Nigeria. It therefore concludes that selection strategies affect the management and performance of organizations. The paper recommends that more attention should be given to selection procedures/strategies in the recruitment process since they help to get the right and qualified persons for the vacant jobs in an organisation.And that selection of candidates should be anchored on merit, competence and similar job characteristic factors as they will improve employee's performance.